Changing Dynamics of Leverage Determinants : A Comprehensive Study of Firms Listed in India - Singh, Amit Kumar; Bansal, Preeti; Latha, K. (Indian Journal of Finance, 2025)
Purpose : This study offered a unique perspective on leverage determinants, examining both the direct influences of firm-level and the direct and indirect influences of industry-level determinants. Methodology : By analyzing annual data of all BSE-listed non-financial 3,620 firms from 1992 to 2023 (31 years), resulting in 35,510 firm-year observations, and using the hierarchical linear model (a statistical method that allows for the analysis of data with a nested structure), we were able to assess multi-level influences of leverage determinants. The study’s comprehensiveness regarding firm-year observations and variables effectively addressed the problem of model misspecification and identified the most significant leverage determinants. Findings : Our results revealed significant firm and industry-level leverage determinants, providing evidence that industry factors strongly and indirectly influenced capital structure decision-making, potentially altering the influence of firm-level factors on leverage. Practical Implications : We demonstrated that the relationship between capital structure and its determinants is hierarchical and not straightforward. These findings have important implications for financial decision-making in Indian firms. Originality : This study questioned the dominant perspective in the existing literature that internal firm factors are primary determinants of capital structure.